Kesetaraan Gender dalam Perspektif Sosiologi Pendidikan: Analisis Peran Sekolah dalam Membangun Keadilan Sosial - Ain, Nisrina Qurrotul; Khasanah, nur (Jurnal Pendidikan Agama Islam, 2025)
Gender equality in Indonesian education faces complex structural and cultural challenges, including stereotypes, unequal leadership representation, and entrenched patriarchal norms within society and educational institutions. A literature review of journals, books, and gender mainstreaming policies indicates that despite increased access to education for women, gender disparities persist through discriminatory practices, social expectations limiting female participation, and limited representation in certain fields. Schools play a strategic role as agents of change by implementing gender-sensitive curricula, providing gender literacy training for teachers, creating inclusive learning environments, and developing community-based programs that foster collaboration, leadership, and empathy. Education serves as a tool for social transformation, shaping critical thinking, enhancing social awareness, and restructuring social systems toward equity. Gender-responsive education contributes to reducing stereotypes, increasing female participation, and building a collective culture that values equality. These findings underscore the need for a holistic approach integrating policy, educational practices, and community engagement to achieve gender justice in education, while supporting the development of an inclusive, democratic, and equitable society.